Membrane Lipids’ Metabolism and Transcriptional Regulation in Maize Roots Under Cold Stress - Zhao, Xunchao; Wei, Yulei; Zhang, Jinjie; Yang, Li; Liu, Xinyu; Zhang, Haiyang; Shao, Wenjing; He, Lin; Li, Zuotong; Zhang, Yifei; Xu, Jingyu (Frontiers in Plant Science, 2021)
Low temperature is one of the major abiotic stresses that restrict the growth and development of maize seedlings. Membrane lipid metabolism and remodeling are key strategies for plants to cope with temperature stresses. In this study, an integrated lipidomic and transcriptomic analysis was performed to explore the metabolic changes of membrane lipids in the roots of maize seedlings under cold stress (5°C). The results revealed that major extraplastidic phospholipids [phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidic acid (PA), and phosphatidylinositol (PI)] were dominant membrane lipids in maize root tissues, accounting for more than 70% of the total lipids. In the transcriptome data of maize roots under cold stress, a total of 189 lipid-related differentially expressed genes (DEGs) were annotated and classified into various lipid metabolism pathways, and most of the DEGs were enriched in the “Eukaryotic phospholipid synthesis” (12%), “Fatty acid elongation” (12%), and “Phospholipid signaling” (13%) pathways. Under low temperature stress, the molar percentage of the most abundant phospholipid PC decreased around 10%. The significantly up-regulated expression of genes encoding phospholipase [phospholipase D (PLD)] and phosphatase PAP/LPP genes implied that PC turnover was triggered by cold stress mainly via the PLD pathway. Consequently, as the central product of PC turnover, the level of PA increased drastically (63.2%) compared with the control. The gene-metabolite network and co-expression network were constructed with the prominent lipid-related DEGs to illustrate the modular regulation of metabolic changes of membrane lipids. This study will help to explicate membrane lipid remodeling and the molecular regulation mechanism in field crops encountering low temperature stress.